Analisis Perilaku Konsumen Menuju Konsumsi Berkelanjutan: Studi Kasus Bisnis Thrifting Lokal di Palembang - Alghifari Mahdi Igamo; Nurin Zodarina; Genta Pratama; Reni Mardiana; Angela Damayanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The focus of this empirical research is the urge to analyze consumer behavioral intentions in purchasing sustainable thrifting products. In this study, the implementation of the Theory of Planned Behavior (TPB) focused on measuring how three variables—Green Apparel Knowledge, Social Impressions, and Fashion Orientation—influence the TPB framework: Attitudes, Subjective Norms, and Perceived Behavioral Control (PBC). The sample in the research was 351 consumers of thrifting products in Palembang City using the Stratified Random Sampling method. Data analysis in this study used partial least squares structural equation modeling (PLS-SEM). The research results show that there is a significant positive relationship between Green Attitudes and Knowledge of Green Clothing and Social Impression. Fashion Orientation has a significant positive relationship with Green Attitude. There is a positive effect between the behavioral intention to use sustainable thrifting clothing and the theory of planned behavior variables, such as green attitudes, subjective norms, and perceived behavioral control.